Inner ear drug delivery using liposomes - Mohammadian, F.; Eatemadi, A.; Daraee, H. (Cellular and Molecular Biology, 2017)
Dysfunction of inner ear can result in from several disease procedures and introduce a possibility for therapeutic intervention. The existence of a blood-cochlear obstacle and round window membrane restricts direct access into the inner ear and following inner ear drug, gene, protein and cell delivery. Several strategies have designed to increase drug delivery to the inner ear. One of main particles for inner ear drug delivery is liposome. Here we reviewed the application of liposomes in inner ear drug delivery.